Pengaruh Investasi Syariah, Sukuk Dan Reksadana Syariah Terhadap Pertumbuhan Ekonomi Indonesia tahun 2011- 2020 - Rahmadhana, Efri; Fadhila Rahma, Tri Inda; Tambunan, Khairina (Universitas Labuhanbatu, 2022)
This study aims to determine how the influence of Shari'ah shares, Sukuk and Shari'ah mutual funds on economic growth. This research is a quantitative research with associative approach. The data used are secondary data obtained through the official website of the Central Statistics Agency (BPS) and the Financial Services Authority ( OJK). The analysis used in this study is multiple linear regression analysis with Ordinary Least Square ( OLS) method using E-Views program version 10.Â From the results obtained, it can be explained that syari'ah shares have a positive but not significant influence on Indonesia's economic growth. Sukuk has a significant positive influence on Indonesia's economic growth. And, Syari'ah mutual funds have a significant influence on Indonesia's economic growth but the influence is negative. In the F test ( simultaneous) there is a simultaneous significant influence between syari'ah shares, sukuk and syari'ah mutual funds on Indonesia's economic growth. Adjusted R-Squared = 0.844152. This shows that the independent variables together are able to give an explanation of the dependent variable by 84.4%. The 15.6% is explained by variables outside the model.